Effect of exogenous spermidine on expression profile of reproductive hormone receptors in mouse ovaries - LONG Shiyun; JIANG Dongmei; CHEN Ziyu; GUAN Cheng; YI Zhixin; KANG Bo (浙江大学学报. 农业与生命科学版, 2017)
The polyamines spermidine and spermine and their precursor putrescine are a class of compounds containing two or more amino groups and participate in the regulation of various physiological and pathological processes by interacting with negatively-charged molecules, such as DNA, RNA and proteins. Recently, increasing studies suggest that polyamines also play important roles in follicular development, ovulation and steroidogenesis in female animals. The spermidine exists ubiquitously in species ranging from yeast to mammals. Recently, studies from our and other laboratories indicated that spermidine is involved in regulating animal reproduction through mediating spermatogenesis, oogenesis, follicular development and ovulation. However, to the best of our knowledge, the effect of the spermidine on the expression levels of hormone receptor genes associated with reproduction is unknown.To demonstrate the effect of the spermidine on the transcription of reproductive hormone receptor genes in mouse ovaries, Kunming mice were administrated with 0.05, 0.10 and 0.15 mg/g (body mass) spermidine by intraperitoneal injection. Ovarian tissue samples were collected after 24 h of spermidine administration. The levels of follicle- stimulating hormone receptor (FSHR), luteinizing hormone receptor (LHR), estrogen receptor 1 (ER1), ER2 and androgen receptor (AR) mRNA expression in mouse ovaries were measured using quantitative real-time polymerase chain reaction.The results showed that the level of LHR mRNA expression in ovaries of mice administrated with 0.05 mg/g spermidine was significantly higher than the untreated control group (P<0.05). The amount of LHR mRNA expression in ovaries of mice administrated with 0.15 mg/g spermidine was significantly lower than the untreated control group (P<0.05). With increasing spermidine administration, a gradually increasing trend was observed in the change of FSHR, ER1, ER2 and AR expression levels. The amount of FSHR, ER1, ER2 and AR genes in ovaries of mice administrated with 0.15 mg/g spermidine was significantly high, compared with the untreated control group, respectively (P<0.05).In conclusion, our present results demonstrate that exogenous spermidine mediates the transcription of genes associated with reproductive hormone receptors in ovaries of mice. It is indicated that spermidine might play an important role in regulating the responsiveness of the ovary to reproductive hormones through an unknown mechanism. Further research is needed to elucidate the mechanism of action of spermidine mediating ovarian functions in animals.